2021
DOI: 10.3390/ijms22031103
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aiolos and Ikaros in the Antitumor and Immunomodulatory Activity of IMiDs in Multiple Myeloma: Better to Lose Than to Find Them

Abstract: The Ikaros zing-finger family transcription factors (IKZF TFs) are important regulators of lymphocyte development and differentiation and are also highly expressed in B cell malignancies, including Multiple Myeloma (MM), where they are required for cancer cell growth and survival. Moreover, IKZF TFs negatively control the functional properties of many immune cells. Thus, the targeting of these proteins has relevant therapeutic implications in cancer. Indeed, accumulating evidence demonstrated that downregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 82 publications
(104 reference statements)
0
20
0
1
Order By: Relevance
“…6D–F ), configuring MLN4924 as a modulator of the NF-kB/IRF4/MICA axis. Moreover, we also analyzed the expression of IKZF3 and IKZF1, two TFs required for MM growth and survival [ 46 ], which are known to negatively control the functional properties of many immune cells [ 46 ], and to repress MICA gene expression in MM [ 35 , 47 ]. As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6D–F ), configuring MLN4924 as a modulator of the NF-kB/IRF4/MICA axis. Moreover, we also analyzed the expression of IKZF3 and IKZF1, two TFs required for MM growth and survival [ 46 ], which are known to negatively control the functional properties of many immune cells [ 46 ], and to repress MICA gene expression in MM [ 35 , 47 ]. As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ikaros zinc finger (Ikzf) transcription factors were recently reported to be important transcription factors that regulated lymphocyte development and differentiation ( 42 ), and were significantly increased in ICOS + cells ( 43 ). Ikzf2 (Helios), a member of the Ikaros transcription regulator family, is associated with Th cell differentiation ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The function of Ikaros protein in T cell differentiation has been revealed, whereas contradictory results were obtained in certain mouse models. Research utilizing T cells possessing germline Ikaros gene mutations demonstrated that Ikaros promotes Th17 and Treg cell differentiation and suppresses the polarization of Th1 ( Cippitelli et al, 2021 ). Nevertheless, in a mouse model in which Ikaros conditioned knockout in mature T cells, the deficiency of Ikaros is related to the acquirement of Th1, Th2, Th17 but not Treg cells ( Lyon de Ana et al, 2019 ).…”
Section: Ikaros Family Signalingmentioning
confidence: 99%
“…Ikaros proteins are identified to serve as suppressors in diverse types of lymphoma or leukemia ( Heizmann et al, 2018 ; Chan, 2019 ), whereas they are overexpressed in other malignancies to maintain cancer cell proliferation and survival, such as in malignant plasma cells, monoclonal gammopathy of undetermined significance, and multiple myeloma (MM) ( Cippitelli et al, 2021 ). Detailed functional analyses showed that Ikaros could excite or suppress oncogenes or tumor suppressors genes; consequently, Ikaros-mediated transcriptional expression of target genes regulates survival and proliferation of cancer cells ( Gowda et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%